Facile synthesis of A2mB2n-type starlike copolymers with two types of V-shaped arms by combination of RAFT, ATRP and ROP processes. (1st May 2015) - Liu, Huanhuan; Jiang, Xiao; Bian, Rongjian; Tong, Min; Tang, Dandan; Zhou, Xiangdong; Zhao, Youliang
Abstract: Controlled synthesis of A2m B2n -type (m ≈ n ≈ 8) starlike copolymers comprising an oligomeric poly(styrene- co -maleimide) core and two types of V-shaped arms individually generated by ATRP and ROP was described. Multistep syntheses involving RAFT copolymerization, end group removal, ATRP of vinyl monomers such as styrene (St), methoxyethyl methacrylate (MEMA) and tert -butyl acrylate ( t BA), and ROP of ε -caprolactone (CL) were used to construct the target miktoarm stars with controlled molecular weight and relatively low polydispersity (PDI = 1.07–1.22). The resultant star copolymers had high bromide functionality and uniform chain length of ATRP-generated arms, evident from chain extension polymerization and cleavage of arms. Meanwhile, a pH-responsive (PAA)2m (PCL)2n star was also obtained by selective hydrolysis. The synthetic strategy via combination of RAFT copolymerization and "core first" approach is versatile in constructing various A2m B2n stars, and this study further paves way for facile synthesis and properties of new types of miktoarm stars. Graphical abstract: Highlights: Styrenic and maleimidic inimers were used to generate novel A2m B2n stars. They had controlled molecular weight and composition and precise microstructure. The high bromide functionality was confirmed by chain extension polymerization. Star copolymers had uniform arm length, evident from cleavage of arms. This study paves way for rapid synthesis of miktoarm stars and their derivatives.